ROLE OF ISOVECTOR-ISOSCALAR COUPLING ON CHARGE RADIUS OF HEAVY AND SUPERHEAVY NUCLEI - Netta Liliani (Program Studi Fisika Universitas Negeri Jakarta, 2022)
We have investigated the effect of the isovector-isoscalar coupling on the finite nuclei and nuclear matter properties, the neutron skin thickness of 208Pb, and the charge radius on heavy and superheavy nuclei calculated by the relativistic mean-field (RMF) model. In this work, we generates two parameter sets, i.e., PTE16 and PTE31. The numbers 16 and 31 denote the isovector-isoscalar coupling terms, while T and E denote the tensor coupling and electromagnetic exchange terms, respectively. We found that PTE16 and PTE31 are compatible with the constraints obtained by R. Essick, et al., arXiv: 2102.10074v1 [nucl-th] (2021). We also found that the increase of the isovector-isoscalar coupling terms gives a significant effect on the binding energy and the charge radius on heavy nuclei except for the charge radius of 208Pb. Increased of the isovector-isoscalar coupling terms make the values of charge radius prediction increase too, but vice versa for the neutron skin thickness and nuclear matter prediction. PTE31 yields symmetry energy J = 31.521 MeV, slope L = 57.643 MeV, and neutron skin thickness = 0.21419 fm. While the β2 correction (for deform nuclei) does not always give a significant effect on the charge radius.